Investigation of composites of polymers and Mo6S2I8 nanowires. Issue 5 (6th February 2014) - Park, Ji Hyun; Jo, HyeRan; Seong, Chae‐Yong; Kim, Kyung Ho; Mrzel, Ales; Scalia, Giusy; Park, Yung Woo
<x xml:space="preserve">Abstract</x> We have dispersed Mo6S2I8 nanowires in different types of polyvinyl alcohol (PVA), polystyrene sulfonate (PSS) and surfactants, analyzing their effect on the quality of the dispersion. Raman spectroscopy was employed to investigates the nanowires from suspensions as well as in films. I–V characteristics of networks of nanowires, deposited from suspensions stabilized by PSS, were measured as function of temperature, observing, in the linear region, a variable‐range hopping behavior typical of disordered systems.